THE SOCIAL WORK IN THE FAMILY HEALTH STRATEGY: AN INTEGRATIVE REVIEW (Cadernos ESP, 2024)
The work aims to present a theoretical production of Social Work about the Family Health Strategy. This is an integrative review study and for its construction, publications from the electronic databases of Latin American and Caribbean Literature in Health Sciences (Lilacs) and the Scientific Electronic Library Online (Scielo) were used. The sample totaled 07 published articles, where around 71% were extracted and located in SCIELO and around 29% were extracted and located in LILACS. Primary Care, being one of the entry points for users to access the SUS, must contain professionals who know the health and social problems of the population in its territory, therefore, if it works to guarantee rights, constantly reviewing the way of thinking and act, given that they are people weakened by the system, who often have their basic rights denied.